2018
DOI: 10.1371/journal.ppat.1007229
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages inhibit Aspergillus fumigatus germination and neutrophil-mediated fungal killing

Abstract: In immunocompromised individuals, Aspergillus fumigatus causes invasive fungal disease that is often difficult to treat. Exactly how immune mechanisms control A. fumigatus in immunocompetent individuals remains unclear. Here, we use transparent zebrafish larvae to visualize and quantify neutrophil and macrophage behaviors in response to different A. fumigatus strains. We find that macrophages form dense clusters around spores, establishing a protective niche for fungal survival. Macrophages exert these protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
159
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(186 citation statements)
references
References 72 publications
20
159
0
Order By: Relevance
“…These results suggest that neutrophil recruitment and function at the site of infection are important for controlling A. nidulans infection in both vertebrates. Furthermore, results are in agreement with studies on A. fumigatus which show that virulence is as much a strain-dependent as it is a host-dependent trait (24,37,39,51). Furthermore, the tested phenotypes and genome mutations appear to not correlate with strain virulence, although sample size has to be increased in order to confirm this in future studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results suggest that neutrophil recruitment and function at the site of infection are important for controlling A. nidulans infection in both vertebrates. Furthermore, results are in agreement with studies on A. fumigatus which show that virulence is as much a strain-dependent as it is a host-dependent trait (24,37,39,51). Furthermore, the tested phenotypes and genome mutations appear to not correlate with strain virulence, although sample size has to be increased in order to confirm this in future studies.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in agreement with studies in A. fumigatus that have described great strain heterogeneity in traits such as growth, fitness and enzyme secretion between different environmental and clinical isolates (24, 37). Indeed, the number of SNPs, obtained during strain pairwise comparison, in the genomes of different A. fumigatus strains, range between ~13,500 (24) and ~50,000 (38, 39). Strain heterogeneity has therefore mainly been investigated in environmental and clinical isolates of A. fumigatus, whereas similar studies have not been carried out for A. nidulans isolates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is only when dormancy is broken and germination occurs that this surface layer is breached and host defenses are activated 17 . Other studies in immunosuppressed mice showed that an A. fumigatus isolate with slower germination survived in macrophages and was more virulent than an isolate with faster germination 18,19 . A bet-hedging strategy built on variation in germination rate could allow slow germinators within a population of A. fumigatus conidia to avoid the host immune system and initiate infection.…”
mentioning
confidence: 96%
“…We find that A. nidulans is 237 significantly more virulent than A. fumigatus in p22 -/larvae but not in a generally 238 immunocompromised or neutropenic host.Interestingly, A. fumigatus caused only a low level of 239 death in p22 -/larvae despite being the most frequently isolated fungus from CGD patients (King 240 et al, 2016). The relatively weak virulence of A. fumigatus could be a result of strain variation, 241 which can have a significant impact on host survival (Amarsaikhan et al, 2014, Knox et al, 2016, 242 Kowalski et al, 2016,Rizzetto et al, 2013, Rosowski et al, 2018. Remarkably, rescuing p22 phox 243 function specifically in neutrophils was sufficient to reduce invasive fungal growth but did not 244 affect spore germination.…”
mentioning
confidence: 99%